Germinação de sementes, emergência e recrutamento de plântulas de dez espécies arbóreas das várzeas das reservas de desenvolvimento sustentável amanã e Mamirauá, Amazônia Central - Conserva, Auristela dos Santos (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
The high variation on the dynamics of the Amazon River and its tributaries lead to the formation of patches composed of many sites of different ages. These sites are susceptible to variations on flooding period, so that the organisms of the flooded forests have adaptations and strategies that enable them to survive on these areas, both during aquatic and terrestrial phases. There is a variety of environmental stress conditions to which plant species are submitted, and an equivalent number of possible responses. However, knowing the nature and duration of the major stresses in the environment, it s possible to recognize the correlated response of plants to these conditions. These responses are called syndromes or colonization strategies. In order to understand the complexity of such interactions, some aspects of whitewater floodplain (hereafter várzea ) trees were investigated, such as: fruit and seeds morphology, germination types, the behavior of several species concerning their survival strategies (velocity and distribution of germination frequencies; morphological types, and sapling recruitment patterns), and how these characteristics appear on different successional stages of várzea forests (early, late secondary and climax stages of low varzea and climax of high varzea). Among ten studied species: Ficus anthelmintica, lex. inundata, Duroia duckei, Piranhea trifoliata e Ocotea cymbarum have fruits as dispersion units, while Calycophyllum spruceanum, Pseudobombax munguba, Laetia corymbulosa, Tabebuia barbata e Hura crepitans, have seeds as dispersion units. In general, all studied species have more than one kind of dispersion syndrome. The relation between seed size, successional stage on várzea forests, and initial morphology showed a trend towards smaller phanero-epigeal- foliaceousPEF saplings (< 10 cm), produced by small seeds with few nutrient content, while phanerohypogeal- reserve PHR crypto- epigeal-reserve CER, and crypto- hypogeal-reserve CHR saplings tends to be bigger (> 40 cm), and produced by bigger seeds with good nutrient reserves. Although the size of seeds showed direct influence on the initial size of saplings, this last characteristic did not change the recruiting pattern of saplings and their establishment on the field. In the field survey were recorded a total of 1.218 seedlings from eight speceis in a area of 1760 m2 with the maximum number of 676 seedlings from Gavão area end the minimum of 120 from Dórico area. Pseudobombax munguba, Ilex inundata e Piranhea trifoliata were the most abundants species with 358, 296 e 298 seedlings respectively. The effect of the interaction between flooding period and the different levels of relative radiation were significant for four of the eight investigated species Pseudobombax munguba, Laetia corymbulosa, Duroia duckei e Piranhea trifoliata the best germinability under 11% of light radiation. The increase of radiation associated with the flooding duration reduced the germinability of P. munguba D. duckei e P. trifoliata species from early, late and climax successional stages from low varzea forest. The velocity of emergence in seedlings from studied species can be separated in two groups were Calycophyllum spruceanum and Pseudobombax munguba were those with high velocity of emergence, and consequently with higher vigor on control treatment. This species emerges, in average, at least one sapling per day. For the other species, given their low velocity of emergence, showed less than one sapling emerged after a five days period. The investigated characteristics seem to promote strategies efficient, for maintenance of the populations of the evaluated species. A time that Ficus anthelminthica, Calycophyllum spruceanum, Pseudobombax munguba, Ilex inundata, Duroia duckei, Laetia corymbulosa, Tabebuia barbata, Piranhea trifoliata, Ocotea cymbarum and Hura crepitans, are cited between the 60 more important species, with greater IVI inside of the varzea forests of all Amazonian Basin.
Keywords: Dispersão; morfologia de frutos e sementes; Germinação de espécies arbóreas; Amanã; Mamiraurá; Florestas de várzea